TREINAMENTO DOS MUSCULOS INSPIRATÓRIOS NO DESEMPENHO DE CORREDORES ATLETAS DE RUA (REMUNOM, 2025)
Road running has significantly increased in recent years due to being a low-cost and easily accessible sport, with no distinction of age or gender. In addition to being a simple sport, it can be practiced at any time and place. Inspiratory muscle training (IMT) has been used to improve the performance of athletes, focusing on strength and power gains. Its application has proven to be a viable strategy to create favorable conditions for improving respiratory capacity. The goal was to evaluate the effect of inspiratory muscle training on the performance of road running athletes. Six road running athletes participated in the study. Before starting the training, they completed a sociodemographic and lifestyle questionnaire, followed by a functional assessment (respiratory function evaluation, functional capacity, and performance). IMT was performed over 12 sessions, three days a week, for 4 weeks. The protocol consisted of 3 sets of 10 repetitions using the PowerBreathe inspiratory muscle trainer. After completing the IMT protocol, the functional assessment was repeated. In the respiratory evaluation, a significant improvement in inspiratory muscle strength was observed, with no significant difference in expiratory flow and thoracic mobility after IMT. In the functional capacity assessment, a significant increase was found after IMT. In the 2km running performance, improvements were observed in time and running pace, though not significantly. Inspiratory muscle training promotes an increase in inspiratory muscle strength and may improve the performance of road runners.